ANALYSIS OF PUJA DANCE MUSIC - Kusumo, mauritius tamdaru; Utomo, Budi (Institut Seni Indoensia Surakarta, 2025)
This study aims to examine textually and contextually the Puja Dance Music presented in the ritual of the Puja Bakti Agung Asadha. This research was carried out qualitatively with data collection methods such as document studies, observation of performance recordings and interviews. The analysis in this study relies on a formal aesthetic understanding for multi-layered analysis and the drawing of conclusions presented descriptively. The results obtained from the results of the analysis are that Puja Dance Music textually functions as a dance accompaniment that frames the dramatic presentation of the Puja Dance performance in a liturgical context. Contextually, the music works of the Puja Dance are arranged as a form of contribution to the development of religious performance arts in the country.